1989
DOI: 10.1002/j.1460-2075.1989.tb03617.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural polymorphism of homopurine-homopyrimidine sequences: the secondary DNA structure adopted by a d(GA.CT)22 sequence in the presence of zinc ions.

Abstract: In this paper, we have analysed the conformational behaviour shown by the homopurine–homopyrimidine alternating d(GA.CT)22 sequence cloned into SV40. Our results show that, in the presence of zinc ions, the d(GA.CT)22 sequence adopts an altered secondary DNA structure (*H‐DNA) which differs from either B‐DNA or H‐DNA. Formation of *H‐DNA is facilitated by negative supercoiling and does not appear to require base protonation, since it is induced at neutral pH by approximately 0.4 mM ZnCl2. The patterns of OsO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…Tetraplexes are only formed by the (G + A) strands of DNA where guanine dominates. 21 This, for example, concerns (GGGA) 5 or (GGA) 7 but not (GGAA) 5 , (GAA) 7 , and (GAAA) 5 . 21 Our data are also not consistent with a hairpin dimer of (GA) n containing guanine tetrads, a conformation which was proposed on the basis of a UV resonance Raman study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraplexes are only formed by the (G + A) strands of DNA where guanine dominates. 21 This, for example, concerns (GGGA) 5 or (GGA) 7 but not (GGAA) 5 , (GAA) 7 , and (GAAA) 5 . 21 Our data are also not consistent with a hairpin dimer of (GA) n containing guanine tetrads, a conformation which was proposed on the basis of a UV resonance Raman study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also informative that the homoduplex of (GA) n can coexist with a homoduplex of (TA) n in a single DNA molecule. 19 (GATA) 5 even can, as a whole, adopt either a homoduplex characteristic of (TA) 10 or (GA) 10 depending on the salt concentration, and switch between them reversibly. 19 We think that the starting structure to model the homoduplex of (GA) n should be sought in parallel-stranded pieces of crystal [35][36][37][38] or NMR solution 39,40 structures of purine-rich molecules of DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding to the bases can destabilize DNA and cause local denaturation of the DNA double helix. It has been shown that some local DNA structures such as intramolecular triplexes (Beltran et al, 1993;Bernues et al, 1989), hairpins (Martinez-Balbas and Azorin, 1993) and homopurine duplexes (Ortiz-Lombardia et al, 1995) are stabilized by zinc. In the presence of zinc, formation of kinks in DNA molecules have been observed (Han et al, 1997a,b;Laundon and Gri th, 1987).…”
Section: Dna-zinc Bindingmentioning
confidence: 99%
“…Purine motif triple helices usually require the presence of divalent ions, but not all divalent ions have equivalent efficiencies. For instance Mg 2+ ions which have been used in the above recalled studies are unable to induce R•R.Y triplexes in d(GA.TC) n sequences (29) while Zn 2+ ions do (30). In many cases Zn 2+ ions have proved to be particularly efficient in antiparallel triple helix stabilization (31)(32)(33).…”
Section: Introductionmentioning
confidence: 96%